تقرير أقل اًلبلداًن نمواًً 2024 - UN Trade; Development (United Nations, 2025)
Policymakers in the least developed countries are under pressure to transform carbon markets into a viable pathway to deliver on the Sustainable Development Goals and low-carbon structural transformation. This begs the question of whether and how these markets can both address the unique challenges of these countries and help them to contribute to global efforts to mitigate climate change. The report highlights the outcomes of past and current participation by least developed countries in carbon markets, and identifies opportunities and risks from the emerging framework for carbon markets under the Paris Agreement. Towards the maximization of the benefits of carbon markets for LDCs, the report provides actionable recommendations for least developed country policymakers and climate negotiators, and for their development partners